2021
DOI: 10.24323/akademik-gida.927462
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Biscuits Fortified with Pomegranate Peel

Abstract: In this study, some chemical, physical and sensory properties of biscuits prepared with various substitution ratios (0, 6, 12 and 18%) of pomegranate peel were determined. To this end, pomegranate peel substitution did not cause a significant alteration in the protein, fat and ash contents of the biscuits. Results show that the antioxidant activity (from 5.06 μmol TE/100g to 288.38 μmol TE/100g), total phenolic content (from 56.49 mg GAE/100g to 1108.35 mg GAE/100g), soluble, insoluble and total dietary fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The results show that pomegranate and orange peel powder have an effect on all sensory properties of the cake when compared to the control. These findings are consistent with those of Urganci and Isik [124], who recommended using pomegranate peel powder formulation rates of up to 18% in the formulation and discovered the possibility of using pomegranate peel powder in biscuits to enhance nutritional values. Furthermore, pomegranate peel powder will be accelerated as human feed, gaining more value as a waste product.…”
Section: The Effect Of Shelf Life On Sensory Evaluation Of Cake Suppl...supporting
confidence: 91%
“…The results show that pomegranate and orange peel powder have an effect on all sensory properties of the cake when compared to the control. These findings are consistent with those of Urganci and Isik [124], who recommended using pomegranate peel powder formulation rates of up to 18% in the formulation and discovered the possibility of using pomegranate peel powder in biscuits to enhance nutritional values. Furthermore, pomegranate peel powder will be accelerated as human feed, gaining more value as a waste product.…”
Section: The Effect Of Shelf Life On Sensory Evaluation Of Cake Suppl...supporting
confidence: 91%
“…Additionally, the mixed sample benefited from the synergistic properties of hydrocolloids, which acted synergistic properties against starter culture and microbial flora growth that prevented changes in pH in the Doogh structure (Kamdem et al, 2020; Ranadheera et al, 2010; Williams & Phillips, 2021). Also, Solltani et al (2012) pointed out that pH of Iranian drink (Doogh) was lower than 4.5. These results are in agreement with this project (Soltani et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Also, Solltani et al (2012) pointed out that pH of Iranian drink (Doogh) was lower than 4.5. These results are in agreement with this project (Soltani et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The protein, fat, and ash content of the biscuits were unaffected by the addition of pomegranate peel, but the antioxidant activity, total phenolic content, and dietary fiber content were all raised. However, it was concluded that powder substitution should not be increased by more than 12% as it will contribute to the enhanced sour and bitter taste of the biscuits making them inedible (Urganci & Fatma, 2021 ). Date bars containing date paste, nuts, and roasted gram, when fortified with pomegranate and apple peels, showed that both can be used as therapeutic agents against degenerative disorders due to oxidative stress due to their high polyphenolic content and associated antioxidant activity (Ranjha et al., 2020 ).…”
Section: Food Applicationsmentioning
confidence: 99%